Nutritional profile and glycemia of school adolescentes (Research, Society and Development, 2020)
The objective was to evaluate the nutritional profile and glycemia of adolescents from public and private schools in Teresina-PI. This is a cross-sectional, comparative, quantitative study conducted with 66 adolescents between the ages of 14 and 15 of both sexes of public and private schools. A sociodemographic and weekly food frequency questionnaire was applied; the nutritional status was evaluated by anthropometric measurements and the postprandial capillary glycemia test was performed. There was a prevalence of female (56.1%), active (62.1%), normal glycemia with increase in proportion to the increase in BMI in both schools, a correlation between glycemia and consumption of soft drinks (p = 0.002), vegetables (p = 0.003) and vegetables (p = 0.003), especially the private school. It was concluded that the studied adolescents presented adequate nutritional status, blood glucose and food intake, and that there was no difference between schools. The importance of monitoring risk factors for chronic diseases and actions that encourage active behavior, healthy eating and change of habits in the school environment to promote a healthier life should be emphasized.